Fertility in South Dublin a Century Ago: A First Look - Timothy Guinnane; Carolyn Moehling; Cormac Ó Gráda (Yale University, Economic Growth Center, 2001)
Ireland's relatively late and feeble fertility transition remains poorly-understood. The leading explanations stress the role of Catholicism and a conservative social ethos. This paper reports the first results from a project that uses new samples from the 1911 census of Ireland to study fertility in Dublin and Belfast. Our larger project aims to use the extensive literature on the fertility transition elsewhere in Europe to refine and test leading hypotheses in their Irish context. The present paper uses a sample from the Dublin suburb of Pembroke to take a first look at the questions, data, and methods. This sample is much larger than those used in previous studies of Irish fertility, and is the first from an urban area. We find considerable support for the role of religion, networks, and other factors stressed in the literature on the fertility transition, but the data also show a role for the social-class effects downplayed in recent discussions.
Keywords: J1; N3; 330; Ireland; Fertility; Demography; Fertilität; Irland; Demographischer Übergang